1993
DOI: 10.1007/bf00138552
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated solute concentrations on the fermentation of lactose by Kluyveromyces marxianus Y-113

Abstract: The effect of increased solute concentrations on the fermentation of lactose to ethanol by Kluyveromyces marxianus Y-113 was investigated in batch culture. Elevated concentrations of lactose, maltose, NaCl or ethanol all inhibited the fermentation but to varying extents. Maltose was the least inhibitory of the solutes added while ethanol, and in particular the combination of high ethanol and high lactose concentrations, had the greatest inhibitory action. A maximum concentration of 45-52 g/l ethanol was achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…At 48 h, the ethanol concentration was 23.2 g/l, the productivity 0.48 (g/l)/h, and the yield 23% of the theoretical yield. The decrease of ethanol concentration involved several factors such as high osmotic pressure conditions and high temperatures 19 . On the other hand, the decrease of sugar concentration to 160 g/l reduced the ethanol concentration.…”
Section: Optimization Of Ethanol Fermentation In Shaking Flask Cultivmentioning
confidence: 99%
“…At 48 h, the ethanol concentration was 23.2 g/l, the productivity 0.48 (g/l)/h, and the yield 23% of the theoretical yield. The decrease of ethanol concentration involved several factors such as high osmotic pressure conditions and high temperatures 19 . On the other hand, the decrease of sugar concentration to 160 g/l reduced the ethanol concentration.…”
Section: Optimization Of Ethanol Fermentation In Shaking Flask Cultivmentioning
confidence: 99%
“…However, incomplete or slow fermentations have been observed for many Kluyveromyces strains, when concentrated whey or lactose-enriched substrates have been employed [12,32]. These effects have been attributed variously to the toxicity of the ethanol produced and/or to inhibition by high salt concentrations, resulting in elevated osmotic pressure [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, incomplete or slow fermentations have been observed for many Kluyveromyces strains, when concentrated whey or lactose-enriched substrates have been employed [12,32]. These effects have been attributed variously to the toxicity of the ethanol produced and/or to inhibition by high salt concentrations, resulting in elevated osmotic pressure [12]. Furthermore, it has been reported that increases in lactose concentrations can lead to the accumulation of pyruvate resulting from the greater glycolytic flux in these yeasts, thereby causing a reduction in final biomass yields [3].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the energy savings achieved through the reduction of the expensive cooling and sterilization processes. Several reports revealed inhibitory effects and related problems in the fermentation of concentrated carbon, particularly slow fermentations and high residual sugar (Gawel & Kosikowski, 1978;Janssens et al, 1983;Vienne & von Stockar, 1985;Kamini & Gunasekaran, 1987;Grubb & Mawson, 1993;Dale et al, 1994;Silveira et al, 2005;Zafar et al, 2005;Ozmihci & Kargi, 2007). Main cause of these problems is osmotic sensitivity and low ethanol tolerance (Janssens et al, 1983;Vienne & von Stockar, 1985;Grubb & Mawson, 1993;Zafar et al, 2005).…”
Section: Isolation and Primary Screening Of Yeastmentioning
confidence: 99%